RANCANG BANGUN MESIN PERAJANG PELEPAH SAWIT UNTUK PAKAN TERNAK - Desmarita Leni; Zulbahri Bahar; Veny Selviyanty (Jurnal Teknik Mesin, 2018)
The design of the palm frond chopper machine for animal feed is a vocational application. The purpose of making palm frond chopper machines for animal feed is to help the community open a business field, especially the development of livestock production who grow oil palm. It is an expected that the palm frond chopper machine can help the community to improve economic output. This machine has dimensions of 600 mm x 500 mm where the working principle of the machine is to cut using a blade to accelerate the cutting process. Blade rotation is a obtained by using 3 HP motor and using pulley 5 inch as a tool to rotate the knife plate.